A high-performance flexible aqueous silver–zinc rechargeable battery based on AgNP/CNT-graphite paper and ZnNF-graphite paper. (August 2021) - Yin, Qisheng; Chen, Libao; Chen, Yuejiao; Zhan, Feng
Abstract: The flexibility and safety of energy storage devices have drawn wide attention due to rapid development of wearable electronics. Silver-zinc (Ag–Zn) battery are one of the promising aqueous zinc-based battery with non-toxic environment, stable output voltage and high energy density. Flexible electrode plays a key role in excellent mechanical and electrochemical properties of batteries. In this work, silver nanoparticles/carbon nanotubes-graphite paper (AgNP/CNT-Gp) cathode is prepared by double-side coating on graphite paper. The mixed silver nanoparticles and carbon nanotubes construct a 3D spatial conductive network to contribute excellent electrochemical performance for Ag–Zn battery. The quasi-solid-state Ag–Zn battery shows area specific capacity of 1.268 mAh/cm 2 and excellent energy density of 1.913 mWh/cm 2 at current density of 1 mA/cm 2 . The battery not only represents superior electrochemical properties, but also demonstrates perfect flexibility. We use the quasi-solid-state Ag–Zn battery to successfully light up an indicator composed of 9 LED bulbs, which can still work when the battery is completely folded. Highlights: A flexible Ag–Zn battery is fabricated by using graphite paper as current collector. Mixed silver nanoparticles and carbon nanotubes construct a 3D conductive network. High area specific capacity and energy density are exhibited by the flexible battery. The flexible Ag–Zn battery works well under completely folded.